Low Strain Rates Behaviour of Carbon Nanotube Enhanced Bagasse-Epoxy Polymer Composites for Dynamic Structure Applications - Tan, Ke Khieng (Curtin University, 2020)
The demand for the high-performance natural fibre reinforced polymer composite is growing day by day. However, uneven micro-sized natural fibre like bagasse has causes low performance due to sensitive crack initiation and propagation in composite at higher tensile cross-head speed. In this research, further reinforcement using single-wall carbon nanotube was able to enhance tensile properties of bagasse composite to certain extend and achieving high strength to weight ratio at higher tensile crosshead speed.